Application of Licensing Services Electronic Based Construction Services Business - Umiyati , Sri; Tamrin , M. Husni; Maharani, Debby Gita (Advances in Social Sciences Research Journal, 2019)
This research main goals are describring and analyzing service application based on electronic (Descriptive Study on Bussiness Permit Licensing for Construction Service in One-stop Integreted Service Unit in Surabaya). This research uses descriptive method with qualitative approachment. The theory that is used for analyzing on this research is e-Service Quality theory that consist of 7 dimension that are Website Design, Reliability, Responsiveness, Security/Privacy, Costumization, Information, and Ease of Use. The research result shows that application of Business Permit Licensing based on electronic is good. The dimensions that have shown the application of electronic-based services are good, namely in the dimensions of Responsiveness, Security / Privacy, Customization, Information, Ease of Use. The dimensions that show the application of services that are still not good, namely the dimensions of Website Design and Reliability.